2011
DOI: 10.1371/journal.pone.0021911
|View full text |Cite
|
Sign up to set email alerts
|

CCN2 Is Required for the TGF-β Induced Activation of Smad1 - Erk1/2 Signaling Network

Abstract: Connective tissue growth factor (CCN2) is a multifunctional matricellular protein, which is frequently overexpressed during organ fibrosis. CCN2 is a mediator of the pro-fibrotic effects of TGF-β in cultured cells, but the specific function of CCN2 in the fibrotic process has not been elucidated. In this study we characterized the CCN2-dependent signaling pathways that are required for the TGF-β induced fibrogenic response. By depleting endogenous CCN2 we show that CCN2 is indispensable for the TGF-β-induced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 54 publications
2
63
1
Order By: Relevance
“…We speculate that CCN1 binding to these integrins may be necessary for enhanced TGF-b1/SMAD3 signaling. Similar to findings of our study with CCN1, there are reports of crosstalk of the TGF-b/SMAD pathway with other matricellular proteins, specifically secreted protein acidic and rich in cysteine (50), and connective tissue growth factor (connective tissue growth factor; CCN2) (51,52).…”
Section: Discussionsupporting
confidence: 90%
“…We speculate that CCN1 binding to these integrins may be necessary for enhanced TGF-b1/SMAD3 signaling. Similar to findings of our study with CCN1, there are reports of crosstalk of the TGF-b/SMAD pathway with other matricellular proteins, specifically secreted protein acidic and rich in cysteine (50), and connective tissue growth factor (connective tissue growth factor; CCN2) (51,52).…”
Section: Discussionsupporting
confidence: 90%
“…It was shown that TGF-b activates Smad1 and Erk1/2 pathways in fibroblasts (45). Activation of Smad1/5/8 by TGF-b was also reported for C2C12 mouse mesenchymal stem cells and HepG2 human hepatocellular carcinoma cells (46), endothelial cells (47), and smooth muscle cells (48).…”
Section: Discussionmentioning
confidence: 72%
“…6A and B). Previously it was shown that the classical Smad1 pathway plays a role in the TGF-β1 regulation of collagen and α-SMA expression (11). We then determined the activation of Smad1 pathways in response to TGF-β1 stimulation.…”
Section: Ccn3 Induces Cell Apoptosis and Downregulates Collagen I Comentioning
confidence: 99%
“…Findings of previous studies provided strong evidence that CCN2 plays a role in scars, particularly as a co-factor of TGF-β1 (12). In addition, CCN2 is likely to mediate the ability of TGF-β1 to stimulate ECM synthesis and is a moderate inducer of collagen synthesis (11,13). CCN2 and CCN3 are opposing factors in regulating collagen promoter activity and the secretion of this ECM protein.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation